2021
DOI: 10.1038/s41467-021-26672-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of SARS-CoV-2-breakthrough infections to time-from-vaccine

Abstract: The short-term effectiveness of a two-dose regimen of the BioNTech/Pfizer mRNA BNT162b2 severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine was widely demonstrated. However, long term effectiveness is still unknown. Leveraging the centralized computerized database of Maccabi Healthcare Services (MHS), we assessed the correlation between time-from-vaccine and incidence of breakthrough infection between June 1 and July 27, the date of analysis. After controlling for potential confounders as age … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
177
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(202 citation statements)
references
References 16 publications
12
177
2
1
Order By: Relevance
“…The significant decline of nAb response against the delta variant observed among post 3 months’s BNT162b2 vaccinees in our study provides a possible reason for the increased breakthrough infections observed globally. The report that BNT162b2 recipients who completed their vaccination between Jan-April in Israel had an increased risk of breakthrough infections with delta variant is in line with our interpretation 29 . Thus, our test’s ability to detect variant specific nAb waning effects among a vaccinated population provides an extremely valuable tool to pre-emptively test nAb responses against emerging variants and through this inform booster planning and public health management.…”
Section: Discussionsupporting
confidence: 89%
“…The significant decline of nAb response against the delta variant observed among post 3 months’s BNT162b2 vaccinees in our study provides a possible reason for the increased breakthrough infections observed globally. The report that BNT162b2 recipients who completed their vaccination between Jan-April in Israel had an increased risk of breakthrough infections with delta variant is in line with our interpretation 29 . Thus, our test’s ability to detect variant specific nAb waning effects among a vaccinated population provides an extremely valuable tool to pre-emptively test nAb responses against emerging variants and through this inform booster planning and public health management.…”
Section: Discussionsupporting
confidence: 89%
“…A high incidence of breakthrough infection among vaccinated healthcare workers and the general population has also been described. 7,8 As such, the ACIP recommended a booster mRNA vaccine dose six months following completion of the original two-dose vaccine series for all adults. Booster doses have reduced incidence of infection and severity of illness.…”
Section: Discussionmentioning
confidence: 99%
“…While protection against hospitalizations and deaths remained robust, several studies appeared to show a decline in protection against COVID-19 infections a few months after the initial vaccination. In a retrospective study in Israel, rates of breakthrough infections amongst fully vaccinated patients with the Pfizer-BioNTech vaccine were considerably higher among those vaccinated earlier than those who were immunized later [11]. Analysis of an observational study among fully vaccinated nursing home residents revealed that the vaccine efficacy dropped from 74.7% to only 53.1% in a few months [12].…”
Section: Introductionmentioning
confidence: 98%